Analysis of entry and exit signals applied for futures trading strategy - Vandas, Martin (2011)
This bachelor thesis is based on creating a simple speculation strategy applied for futures markets. The first part of this work describes futures contracts, characteristics of subjects who trade with them and risks connected with futures trading. The next parts present entry and exit signals of modelled trading strategy and their effects on the final measured results. The goal of this work is to find out, which part of the process of creating strategies is more important and whether the combination of both ensures better trading results, concerning other important factors.